Optimizing Logistics Distribution in Archipelagic Economies: A Case Study of North Sulawesi - Wijayanti, Dian; Widiawati, Sarovah (Indonesian Scientific Publication, 2024)
This study aims to examine the determinants of logistics distribution efficiency in North Sulawesi, Indonesia, an archipelagic region with unique geographical challenges. Using a quantitative explanatory design, data were collected through structured questionnaires from 55 purposively selected logistics stakeholders, and analyzed using multiple linear regression with validity and reliability testing. The results show that delivery time has the strongest positive influence on distribution efficiency (β = 0.482; p = 0.001), followed by infrastructure and technology (β = 0.317; p = 0.021), while distribution cost negatively affects efficiency (β = −0.215; p = 0.034). These findings highlight the critical role of timeliness and technological adoption in overcoming logistical barriers in archipelagic settings. The study contributes by offering practical recommendations for multimodal transport integration, digital adoption, and infrastructure investment to strengthen logistics performance in geographically dispersed economies.